MEDICINAL FRUITS - Karimova, Lobar (Центр Научных Публикаций (buxdu.uz), 2022)
: Remedies made of natural materials are cleaner and more effective than artificially made medical pills. Besides that, they are highly needed for human organism. We should not forget natural medicines including full of vitamins and having a massive impact on our healthy lifestyle and utilize them wisely and in the most effective way.